2014
DOI: 10.1590/1519-6984.17112
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, management and diversity of yam local varieties in Brazil: a study on Dioscorea alataL.

Abstract: Widely spread in the tropics, yams were introduced into Brazil during the colonial period and are currently grown throughout the country. Despite its importance as a pharmacological and food source, there is a lack of studies describing how and where this tuber is grown in Brazil. The aim of this study was to provide an overview of the cultivation and distribution of Dioscorea alata in different Brazilian regions. A total of 63 farmers were visited in different municipalities and communities in four regions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
3
0
5
Order By: Relevance
“…During the collection and subsequent identification of the material in the greenhouse, we observed that sprouted tubers sometimes belonged to other species of Dioscorea, particularly D. alata (Siqueira et al, 2014). It was also observed that 56% of the farmers cultivate only one variety of D. trifida, unlike other species of vegetative propagation, such as cassava (Manihot esculenta), potato (Solanum tuberosum), sweet potato (Ipomoea batatas) (Brush et al, 1981;Salick et al, 1997;Sambatti et al, 2001;Emperaire and Peroni, 2007;Amorozo, 2008;Veasey et al, 2008), where it is customary to keep two or more varieties in the same farm.…”
Section: Distribution and Socioeconomic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the collection and subsequent identification of the material in the greenhouse, we observed that sprouted tubers sometimes belonged to other species of Dioscorea, particularly D. alata (Siqueira et al, 2014). It was also observed that 56% of the farmers cultivate only one variety of D. trifida, unlike other species of vegetative propagation, such as cassava (Manihot esculenta), potato (Solanum tuberosum), sweet potato (Ipomoea batatas) (Brush et al, 1981;Salick et al, 1997;Sambatti et al, 2001;Emperaire and Peroni, 2007;Amorozo, 2008;Veasey et al, 2008), where it is customary to keep two or more varieties in the same farm.…”
Section: Distribution and Socioeconomic Aspectsmentioning
confidence: 99%
“…Among these, only 10 are considered important in human nutrition (Lebot, 2009) (Pedralli, 1988;Bressan et al, 2005;Veasey et al, 2010;Siqueira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…O inhame (Dioscorea spp) é um tubérculo consumido em vários países. No Brasil é cultivado principalmente por agricultores familiares e incorporado em suas dietas (Siqueira et al, 2014). Além disso, possui alto teor de amido, sendo parte dele o amido lentamente digerido, o qual provoca uma elevação drástica na glicemia e teor de insulina no sangue após as refeições (Chen et al, 2017).…”
Section: Introductionunclassified
“…Apesar de o inhame estar no cardápio de diversas civilizações ao longo dos séculos e estar presente desde o início da colonização brasileira, são os nordestinos que assumem a demanda do inhame noBrasil (ANDRADE, 2007). O seu cultivo é na maioria feito por agricultores familiares que o utilizam para enriquecer a alimentação diária(SIQUEIRA et al, 2014). Pesquisas abordam os benefícios do inhame na saúde, no qual apresenta importante valor nutricional por ser uma expressiva fonte de fibras, minerais, carboidratos e vitaminas C e do complexo B, tendo em vista que 30% de sua composição é de amido de qualidade superior à mandioca(PAULA et al, 2012).…”
unclassified